BAHASA SLANG: DAMPAKNYA TERHADAP KEMAMPUAN BERBAHASA INDONESIA YANG BAKU DI KALANGAN MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI PADANG - Gilang Anugrah; Gita Indah Cahyani; Bunga Cahaya Murni; M. Hadi Pratama; Farel Olva Zuve (JURNAL SKRIPTA, 2026)
This study was motivated by the increasing use of slang among university students, which has the potential to affect their ability to use standard Indonesian, particularly students of Indonesian Language and Literature Education at Universitas Negeri Padang, who are expected to serve as models of proper and correct language use. This study aims to analyze the impact of slang usage on students’ proficiency in standard Indonesian in the context of oral communication in academic settings. The research employed a qualitative approach using field observation, and in-depth interviews with students of Indonesian Language and Literature Education. Data were collected through direct observation of students’ language practices in academic environments and through structured interviews to explore the participants’ subjective experiences. Data analysis was conducted through the stages of data reduction, data presentation, and descriptive conclusion drawing. The results indicate that intensive use of slang has an impact on inappropriate word choices, inaccurate sentence structures, mixing of informal and formal registers, and low adherence to standard spelling rules in academic communication. The study concludes that slang has a significant impact on the decline in the accuracy of students’ use of standard Indonesian, thereby highlighting the need for strengthening language development programs in higher education.